2003
DOI: 10.1007/s00431-002-1125-3
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological and clinical aspects of congenital heart disease in children in Tuzla Canton, Bosnia-Herzegovina

Abstract: congenital heart disease is a very significant health problem in Tuzla Canton. It requires urgent measures in terms of organisation of early diagnosis and proper management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
17
1
3

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 8 publications
5
17
1
3
Order By: Relevance
“…The most common cardiac malformation was ventricular septal defect, which is similar to other investigations (9,11,27). These data and data on the structure and frequency of other CHDs, atrial septal defect, pattern ductus arteriosus, tetralogy Fallot are in line with epidemiological population based studies (1,4,5). All syndromic cases and 5 children with other associated non-renal anomalies had CHD, which suggested a genetic cause of this connection.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The most common cardiac malformation was ventricular septal defect, which is similar to other investigations (9,11,27). These data and data on the structure and frequency of other CHDs, atrial septal defect, pattern ductus arteriosus, tetralogy Fallot are in line with epidemiological population based studies (1,4,5). All syndromic cases and 5 children with other associated non-renal anomalies had CHD, which suggested a genetic cause of this connection.…”
Section: Discussionsupporting
confidence: 90%
“…The total birth prevalence of CHD in Europe is 8.1 per 1000 liveborns (3,4), with significant differences (3.9-50 per 1000 liveborns) throughout the world and over time. According to an epidemiological study from 2003, the prevalence of CHD in the Tuzla Canton, Bosnia-Herzegovina, was 6.12 per 1000 liveborns (5). In developed countries it is the main cause of mortality in early childhood and is responsible for one fifth of the total child deaths (6).…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] [ Table 2] shows the prevalence of CHDs in India. [7][8][9][25][26][27][28][29][30] Studies in Chandigarh showed the maximum prevalence of 50.89 per 1000 live births [9] whereas studies in Shimla showed the minimum of 2.25 per 1000 live births.…”
Section: Methodsmentioning
confidence: 99%
“…[8,[20][21][22][23][24][31][32][33][34] The The other frequent defects were found to be ASD (114 patients) with a prevalence of 19.06% followed by TOF with 13.38% (80 patients) and PDA with 9.53% (57 [10] 1975 6.6 UK [11] 1981 5.51 USA [12] 1990 6.60 Bohemia [13] 1999 6.16…”
Section: Methodsmentioning
confidence: 99%
“…2 Meberg et al, [61] Karachi 1987-1992 4 Hassan et al, [62] Central Australia 1993-2000 17. 5 Bolisetty et al, 63 South Australia 1993-2000 12 Annual report 2000 [64] Oman 1994-1996 7.1 Subramanyan et al, [65] Bosnia 1994-1999 6.12 Begic et al, [66] Egypt 1995-1996 1.01 Bassili et al, [67] Shimla 1995 2. 25 Thakur et al, [8] Saudi Arabia 1997-2000 2.4 Alabdulgader [68] New Delhi 2001 4.…”
Section: Classification Of Chdsmentioning
confidence: 99%